Morphology and feeding of the ray Dasyatis guttata (Chondrichthyes:Dasyatidae) in Mucuripe Bay, Ceará State, Brazil - da Silva, Guelson Batista; Viana, Maria Selma Ribeiro; Furtado-Neto, Manuel Antonio A. (Arquivos de Ciências do Mar, 2017)
Morphologic and feeding aspects of Dasyatis guttata rays captured in Mucuripe Bay, Fortaleza, Ceará, were approached in this work. Collections were accomplished in artisanal boats which fish shrimps in an 30 km² area close to Fortaleza, using bottom nets, and artisanal embarkations that use hand lines as fishing art. It was studied a total of 97 individuals: 82 (84,5%) were captured through bottom nets and 15 (15,5%) captured by hand lines. The individuals of D. guttata presented isometric growth, with the values of “ b “ varying between 2,5 and 4,0 (b = 3,066); being the following equation obtained for relationship weight/length: Wt = 2,739 x 10-5 Lt 3,066. Most of the observed individuals’ stomaches (45,4%) were with just ¼ of the filled volume. The number of empty stomaches was also loud (31,9%). Stomaches totally full, with ¾ and half of the filled volume were minority, totalizando 22,7%. Great occurrence of individuals with low IRE (0 or 1), presenting empty stomaches or with up to 25% filled, evidenced that a lot of lines the rays had not fed close to the moment of the capture. They were found in the diet of D. guttata: equinodermats (Holoturidae), sipunculídes (Sipunculus sp.), anelídes poliquetas (Eunicidae), bivalve mollusks and gastropods, and crustaceans, such shrimps of the genus Penaeus and crabs of the genus Callinectes, besides fish of the species Pomadasys corvinaeformis. The presence of a variety of alimentary itens belonging to different animal groups suggests that the ray D. guttata is a opportunist predador.